Evaluating the HERO Ramp-Metering Algorithm with San Diego’s Integrated Corridor Management System Model - Bélisle, François; Torres, Laura; Volet, Pascal; Hale, David K.; Avr, Anjana (Transportation research record, 2019)
The FHWA project “Alternative Designs to Alleviate Freeway Bottlenecks at Merge/Diverge and Weaving Areas” aims at evaluating six different methods to mitigate merge impacts. In this paper, the following ramp-metering algorithms were tested: HEuristic Ramp metering coOrdination (HERO), Asservissement Linéaire d’entrée sur Autoroute (ALINEA), and San Diego Ramp Meter System (SDRMS). These were compared with a “do-nothing” base scenario. The algorithms were tested during a 5 h morning peak period simulation using the integrated corridor management system (ICMS) Aimsun network, a complete and wide-ranging network covering San Diego’s I-15 mainline corridor, on-off ramps and arterial roads. Whereas ALINEA is already included in the base distribution of Aimsun, a new implementation of HERO was programmed from algorithms found in the literature and adapted for use on such a network. Different measures of performance (MOP) were used to assess the efficiency of each algorithm and HERO was found to outperform all the other algorithms: gains of 1.5% over ALINEA and 4% over do-nothing on the mainline average travel time, and gains of 0.5% over ALINEA and 1.5% over do-nothing for the average weighted harmonic speed on all mainline and ramp sections. However, although tests showed that better results can be obtained on the mainline, careful calibration was needed to attain overall positive MOP and not penalize vehicles entering on ramps. The paper concludes with proposed improvements to the original algorithm.